Artificial intelligence systems and the prevention of occupational risks: obligations of the supplier and the employer - Goñi Sein, José Luis (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
The purpose of this paper is to analyse the interplay between the EU Regulation on Artificial Intelligence and the EU regulation on occupational risk prevention with regard to the use of AI systems in the workplace. These two regulations present an identity of reason in terms of risk-based approach and objective, as they seek to mitigate potential risks, but, at the same time, they present notable differences on the scope of risk, giving rise to antinomies. The aim is to resolve these antinomies by making an integrative interpretation of the two regulatory systems and their purposes, in order to foresee which set of obligations must be taken into account, both by the AI provider and the person responsible for the deployment (employer) for its introduction in the market and its commissioning, from the point of view of occupational risk prevention.